Hemoglobin Levels in PRC Blood Products Before and After Shelf Life Period - Ranika Puteri, Orchelanesya Avrilia; Setyaji, Yoki; Setyowatiningsih, Lilik (Academic Hospital Journal, 2025)
Background: PRC is a component found in living creatures, which plays an important role in transporting oxygen and metabolic products to body tissues. PRC transfusion is indicated at Hb levels < 7.0 g/dl, especially in patients with acute anemia. In the transfusion process, before there is a request for blood to be transfused, the blood will be stored in a blood bank. A good blood storage process is needed to maintain the quality of blood products so that they are safe for transfusion. During the storage process, hemoglobin levels in the blood can change. The longer blood is stored, the more red blood cells become fragile and lyse, thereby increasing the concentration of hemoglobin in the blood. This study aims to determine and describe the description of hemoglobin levels in pre- and post-PRC blood products during the shelf life at UDD PMI Rembang Regency.Method: This type of research uses analytical descriptive research and a research design with purposive sampling techniques. The samples used in this study were 30 bags of PRC blood, which met the inclusion and exclusion criteria.Result:  The results of this study showed an increase in hemoglobin levels, with the average pre-storage hemoglobin level being 14.99 g/dl, while the average post-storage hemoglobin level was 17.5 g/dl.Conclusion: In this study, there was an average increase in hemoglobin levels of 2.51 g/dl or 16.74%. This could be caused by temperature, storage time, and anticoagulants.